Advances in the Synthesis and Biological Applications of Enoxacin-Based Compounds - Garba Suleiman; Nabil El Brahmi; Gérald Guillaumet; Saïd El Kazzouli (Biomolecules)
A comprehensive review of advances in the synthesis and biological applications of enoxacin (1, referred to as ENX)-based compounds is presented. ENX, a second-generation fluoroquinolone (FQ), is a prominent 1,8-naphthyridine containing compounds studied in medicinal chemistry. Quinolones, a class of synthetic antibiotics, are crucial building blocks for designing multi-biological libraries due to their inhibitory properties against DNA replication. Chemical modifications at positions 3 and 7 of the quinolone structure can transform antibacterial FQs into anticancer analogs. ENX and its derivatives have been examined for various therapeutic applications, including anticancer, antiviral, and potential treatment against COVID-19. Several synthetic methodologies have been devised for the efficient and versatile synthesis of ENX and its derivatives. This review emphasizes all-inclusive developments in the synthesis of ENX derivatives, focusing on modifications at C3 (carboxylic acid, Part A), C7 (piperazinyl, Part B), and other modifications (Parts A and B). The reactions considered were chosen based on their reproducibility, ease of execution, accessibility, and the availability of the methodology reported in the literature. This review provides valuable insights into the medicinal properties of these compounds, highlighting their potential as therapeutic agents in various fields.